Lomaantha puerariae (Chaetosphaeriaceae), a new species from Guizhou Province, China - Chen, Ya-Ya; Yang, Lin; Liu, Xiao; Long, Xia (Phytotaxa, 2026)
An investigation of fungi associated with medicinal plants in Guizhou Province, China, led to the isolation of two strains from decaying Pueraria wood. Based on phylogenetic analyses of ITS and LSU regions, supported by morphological evidence, a new species, Lomaantha puerariae, is proposed. The combined morphological and molecular phylogenetic data provide strong support for its taxonomic placement. Lomaantha puerariae, identified for the first time as a lignicolous asexual fungus from Pueraria, expands the known diversity of saprobic fungi associated with medicinal plants. This study presents a detailed description, illustrations, and phylogenetic analysis results of the new species.